Development Of Green Economy In The Batik Industry From A Maqashid Sharia Perspective - Khairul Anwar; Susminingsih Susminingsih; A.M. Muh. Hafidz Ma’shum (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2023)
This research aims to analyze the development of the green economy in the batik industry in Pekalongan from a sharia maqashid perspective. This research is field research with a qualitative approach. Data sources use primary data and secondary data. Data collection techniques use observation, interviews, and documentation. The informants consisted of batik entrepreneurs and four employees. The data analysis technique uses data triangulation with stages of data reduction, data presentation, and conclusion. The research results show that the home Pesisir Batik and Dudung Batik industries still need to fully implement the green economy concept. The green economy concept in the business has only been partially implemented, namely in the form of producing naturally coloured batik and minimizing batik waste. Generally, the two batik home industries cover five principles: hifz din, hifz nafs, hifz aql, hifz nasl and hifz mal. Activities to minimize waste pollution include protecting religion, life, and descendants. Likewise, with natural colouring activities on batik. Meanwhile, the sustainability of the batik business after the green economy concept consists of internal and external factors. This research can be used by industries that require consideration of moral values, namely goodness (maslahat) to preserve nature and the survival of human life.